If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -1x + -1 Multiply f * x fx = -1x + -1 Reorder the terms: fx = -1 + -1x Solving fx = -1 + -1x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -1x-1 + -1 Simplifying f = -1x-1 + -1 Reorder the terms: f = -1 + -1x-1
| 4+11x=84 | | 5x-12=-3x+36 | | x-5=i | | x=i | | x-5+x*6=34 | | 10/0.02 | | 3x+31=x+13 | | Log[3](5x-7)=1 | | 4(2x+3)-(5x+2)=73 | | A=1/3A+160000 | | a^2+2ab+b^2=x | | 7x^2+32x-45=0 | | x^2-2x-68= | | x^2-y^2=289 | | 2x+4x=2 | | a+a+b+a+b+a+b= | | 4x+3y+9z-2x+5z-5y= | | 10x-2000+x^2= | | 5x-1=9x-2 | | 7x+b=41 | | 5-2x=2x-3 | | 5(b+2)=35 | | 3(p+5)=21 | | 9(y-2)=9 | | 5(3X+6)+2(x+2)=49 | | 6(x+3)=29(X-1) | | 4(a+7)=44 | | 71.5/5.5 | | t=30-12/5 | | x*.75=2000 | | x*.72=2000 | | x*.75=200 |